Efficacy of iron-biofortified crops - Boy, Erick; Haas, Jere D.; Petry, Nicolai; Cercamondi, C. I.; Gahutu, Jean B.; Mehta, S.; Finkelstein, Julia L.; Hurrell, Richard F. (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Biofortification aims to increase the content of micronutrients in staple crops without sacrificing agronomic yield, making the new varieties attractive to farmers. Food staples that provide a major energy supply in low- and middle-income populations are the primary focus. The low genetic variability of iron in the germplasm of most cereal grains is a major obstacle on the path towards nutritional impact with these crops, which is solvable only by turning to transgenic approaches. However, biofortified varieties of common beans and pearl millet have been developed successfully and made available with iron contents as high as 100 mg/kg and 80 mg/kg, respectively, two to five times greater than the levels in the regular varieties. This brief review summarizes the research to date on the bioavailability and efficacy of iron-biofortified crops, highlights their potential and limitations, and discusses the way forward with multiple biofortified crop approaches suitable for diverse cultures and socio-economic milieu. Like post-harvest iron fortification, these biofortified combinations might provide enough iron to meet the additional iron needs of many iron deficient women and children that are not covered at present by their traditional diets.